2002
DOI: 10.1038/sj.ejcn.1601442
|View full text |Cite
|
Sign up to set email alerts
|

Effect of blackcurrant-, cranberry- and plum juice consumption on risk factors associated with kidney stone formation

Abstract: Objective: To evaluate the influence of plum-, cranberry-and blackcurrant juice on urinary stone risk factors. Design: Investigations were carried out in 12 healthy male subjects aged 18 -38 y. All subjects received a standardized diet formulated according to the dietary recommendations of the German Society of Nutrition. The subjects provided 24 h urine collections in a control, three loading phases. In each loading phase a neutral mineral water was substituted for 330 ml of the particular juice. Results: Cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 19 publications
(16 reference statements)
1
50
1
3
Order By: Relevance
“…This elevation of dietary acidity has recently been reproduced for cranberry and in part for plum ingestion [21]. The authors found a significant fall in urine pH only after cranberry juice, but not after plum juice ingestion [21] which can be explained by a lower dietary PRAL (higher alkalizing potential) of plums compared to cranberries.…”
Section: Consequences For the Estimation Of Net Endogenous Acid Produmentioning
confidence: 79%
“…This elevation of dietary acidity has recently been reproduced for cranberry and in part for plum ingestion [21]. The authors found a significant fall in urine pH only after cranberry juice, but not after plum juice ingestion [21] which can be explained by a lower dietary PRAL (higher alkalizing potential) of plums compared to cranberries.…”
Section: Consequences For the Estimation Of Net Endogenous Acid Produmentioning
confidence: 79%
“…Unsweetened blackcurrant diluted juice increased urinary citrate by 25% over baseline (Kessler et al 2002 experimental M) (23). The consumption of a non citrus alkaline fruit (melon) also has a positive effect in increasing citraturia as compared to citrus fruit consumption (Baia et al 2012 experimental M) (24).…”
Section: Non Citrus Juicesmentioning
confidence: 99%
“…Fruits and fruit juices with high citrate content generally are assumed to deliver an alkali load. However, previously published studies on the influence of different citrate-rich fruit juices/beverages on the risk for stone formation have provided conflicting results, with some beverages decreasing the risk for stones whereas others have either no effect or increase the risk (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). One reason might be the different constituents of various beverages.…”
mentioning
confidence: 77%